Some questions on the creation of the adaptive system of training Masters specializing in management of educational institutions - Yeriomenko, O. A. (Problems of Engineer-Pedagogical Education, 2019)
The article deals with the topical issue of creating the adaptive educational system applied within the process of professional training of Masters specializing in “Educational Institutions Management”. The paper reveals the historical aspect of training Master students specializing in management, defines some features of training Masters in educational institutions management and partially substantiates the adaptive education system with the aim of modernizing the system of training students who are taking their Master’s degree in management. On the basis of an analysis of the educational and vocational training program for Masters specializing in educational institutions management, the author singles out professionally relevant competences, which are integrated taking into account the market requirements and society demand and which must be acquired by students who are taking their Master’s degree. It is determined that the process of training Masters specializing in management of educational institutions requires significant changes based on the adaptive system, which will help provide educational establishments with educational institutions managers, who will be able to reach goals and to make high-quality new decisions in the ever-changing sphere of higher education. The article highlights the need for further development of the adaptive educational system and its implementation into the process of training Masters specializing in management of educational institutions.